نماذج تعلم مهارة الاستماع المنظور النظري بلتعلم السريع (accelerated learning) - Darrin, Abu; Qodir, Abdul (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
The following article tries to present a theme related to maharah istima' learning, where a student can capture a lesson delivered by the teacher, and also in this theme it is related to the theory of accelerated learning, Accelerated Learning is a learning approach that pays more attention to the psychological state of students in learning. The learning concept is based on the findings of a Bulgarian psychiatrist, Dr. George Lozanov. According to Lozanov, the human brain (which is used as the main tool for learning) will only be used effectively if it is in a "fun" state (not under pressure, free and comfortable). Accelerated Learning has several elements, namely SAVI (Somatic, Auditory, Visual and Intellectual). In other words, learning involves the whole self (whole brain). The Accelerated Learning approach is expected to create maharah istina' learning that is fun and motivates student learning without any pressure.